RETRACTION-Determinants Of Crime In Pakistan - Saeed, Hamid; Rajan, Thanachelvan a/I; Butar Butar, Herry Fernandes; Sameem, MAM (Journal of Mental Health and Social Rehabilitation, 2023)
This study investigates the root causes of crime rate in Pakistan, the activities due to which crime is increasing in the country. Variables for this research are crime rate, population growth rate, inflation, household consumption, urbanization, saving (%of GDP) and unemployment. For this purpose, data has been collected for 34 years from the period 1980-2014. The independent variables involved in this research are population growth rate, inflation, household consumption, urbanization, saving (%of GDP) and unemployment whereas the dependent variable is crime rate. For the analysis of data multiple regression has been applied using the SPSS software. The results showed that inflation, population, unemployment, household consumption have positive relation with the crime rate whereas savings is negatively related. The government should take steps to make the environment of country crime free by providing economic incentives to people and by making the law making and implementing departments strong and accountable for what they do.